2023
DOI: 10.1097/hep.0000000000000264
|View full text |Cite
|
Sign up to set email alerts
|

Increasing gallstone disease prevalence and associations with gallbladder and biliary tract mortality in the US

Abstract: Background and Aims: We examined gallbladder and biliary tract mortality predictors in the US National Health and Nutrition Examination Survey (NHANES), 1988-1994, with 31 years of linked mortality data, and gallstone disease prevalence trends and associations in NHANES 2017-March 2020 prepandemic data. Approach and Results: In NHANES 1988-1994, 18,794 participants were passively followed for mortality, identified by death certificate underlying or contributing causes, by linkage to the National Death Index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…[61] In another study, gallstone formation was higher in patients with type-2 diabetes, but this could not be statistically proven. [62] Everson et al found that individuals with hemoglobin metabolism disorders, such as sickle hemoglobinopathy, have an enlarged gallbladder that contributes to the formation of gallstones. [63] A study by Fu et al [64] also suggested that the ratio of beta-lipoprotein and LDL cholesterol to HDL cholesterol is a risk factor for gallbladder stone formation.…”
Section: Discussionmentioning
confidence: 99%
“…[61] In another study, gallstone formation was higher in patients with type-2 diabetes, but this could not be statistically proven. [62] Everson et al found that individuals with hemoglobin metabolism disorders, such as sickle hemoglobinopathy, have an enlarged gallbladder that contributes to the formation of gallstones. [63] A study by Fu et al [64] also suggested that the ratio of beta-lipoprotein and LDL cholesterol to HDL cholesterol is a risk factor for gallbladder stone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient is unique in the fact that he did not fit any of the usual criteria for BS. Upon further literature search, it was seen that Hispanic, specifically Hispanic Americans, are at higher risk of gallstone formation than other races in the United States [6][7][8][9]. Certain genetic factors could explain the formation of gallstones in a Hispanic individual with no apparent risk factors [8].…”
Section: Discussionmentioning
confidence: 99%
“…Acute pancreatitis (AP) is one of the most common non-malignant reasons for hospital admission to gastroenterology, which, with an increasing incidence worldwide, leads to a high burden for healthcare systems [1,2]. The relevance of biliary pancreatitis etiologies in particular, with an annual increase in incidence of 3.6 %, is due to improved endosonographic diagnostics and, at the same time, a global increase in non-communicable metabolic diseases, which favor gallstone formation [1,3,4]. Seasonal and circadian dysregulation and their influence on the development and progression of disease is an under-investigated research area, not only with regard to the pancreas [5].…”
Section: Introductionmentioning
confidence: 99%